Nano-magnetic probing on magnetite (110) - SHVETS, IGOR; MURPHY, SHANE (IEEE Computer Society Press, 2006)
We report our results on the structure and magnetic imaging of Fe3O4 (110) thin films using scanning tunneling microscopy/spectroscopy (STM/STS). Based on atomically resolved STM images we present a model for the observed ridge reconstruction of the surface, in agreement with a bulk-truncated layer containing both octahedral and tetrahedral iron ions. The weak contrast between the tops and the valleys of the ridges in the current map measured withWtips is attributed to the tetrahedral and octahedral character, respectively. We observe a contrast enhancement at the W tip change accompanied by a corrugation enhancement. An antiferromagnetic MnNi tip detects a large contrast between tops and valleys in the current map and two surprising states, at 0.3-V and 0.7-V bias voltages. We attribute the observed contrast to magnetism in agreement with our proposed model.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; antiferroelectric materials